Glioblastoma extracellular vesicles induce the tumour-promoting transformation of neural stem cells. (1st December 2019) - Wang, Jian; Liu, Jialin; Sun, Guochen; Meng, Hengxing; Wang, Jiayin; Guan, Yunqian; Yin, Yiheng; Zhao, Zhenyu; Dong, Xiying; Yin, Shangjiong; Li, Hongwei; Cheng, Yuefei; et al.
Abstract: Recurrent glioblastomas are frequently found near subventricular zone (SVZ) areas of the brain where neural stem cells (NSCs) reside, and glioblastoma-derived extracellular vesicles (EVs) are reported to play important roles in tumour micro-environment, but the details are not clear. Here, we investigated the possibility that NSCs are involved in glioblastoma relapse mediated by glioblastoma-derived EVs. We studied changes to NSCs by adding glioblastoma-derived EVs into a culture system of NSCs, and found that NSCs differentiated into a type of tumour-promoting cell. These transformed cells had distinguished proliferation activity, a high migration rate, and clone-forming ability revealed by CCK-8, wound healing and soft agar clone formation assays, respectively. In vivo assays indicated that these cells could accelerate tumour formation by Ln229 cells in nude mice. Moreover, to explore the mechanisms underlying NSC transformation, single cell transcriptome sequencing was performed; our results suggest that several key genes such as S100B, CXCL14, EFEMP1, SCRG1, GLIPR1, HMGA1 and CD44 and dysregulated signalling may be important for the transformation of NSCs. It is also indicated that NSCs may be involved in glioblastoma recurrence through EV release by glioblastoma in this work. This could help to illuminate the mechanism of glioblastoma relapse, which occurs in a brief period after surgical excision, and contribute to finding new ways to treat this disease. Highlights: Glioblastoma-derived EV-treated NSCs differentiate into tumour-promoting cells. Transformed cells show higher proliferation, migration, and clone-forming ability. These cells also accelerate tumour formation by Ln229 cells in nude mice. Cell sequencing identified key genes and pathways underlying NSC transformation. NSCs might be involved in recurrence through EV release by glioblastoma.